A bibliometric analysis of socially responsible investment sukuk literature - Mahfuzur Rahman; Che Ruhana Isa; Teng-Tsai Tu; Moniruzzaman Sarker; Md. Abdul Kaium Masud (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2020)
Despite the impressive growth of socially responsible investment (SRI) Sukuk (Islamic bond) over the last five years, a handful of comprehensive research is documented in literature. Hence, the aim of this study is to systematically explore and cluster the SRI Sukuk literature to offer comprehensive guidelines for future research. A total of 232 peer reviewed papers from Web of Science database were considered for bibliometric analysis (using VOSviewer software) which are published over the period of 1970-May 2019. This analysis shows SRI Sukuk literature mainly falls in three research clusters: (1) nature of SRI Sukuk, (2) competitiveness of SRI Sukuk, and (3) determinants of SRI Sukuk. However, very few studies have explored the determinants of SRI Sukuk investment. The literature also indicates that, SRI Sukuk research are highly collaborated between Malaysia, Australia, and the USA yet the number is trifling. Thus, exploring motivational factors of SRI Sukuk investment and its impact on the nation's economic development in a cross-country setting would be worthwhile researching.
Keywords: 650; SRI Sukuk; Islamic bond; Bibliometric visualisation; Bibliometric clustering; Systematic literature review; Meta-analysis